Pengenalan Teknologi Informasi Untuk Siswa Kelas 1 - 3 di SD Madison School Mobuya - Mandias, Green Ferry; Moedjahedy, Jimmy Herawan; Adam, Stenly Ibrahim; Putra, Edson Yahuda; Tombeng, Marchel Timothy (Universitas Klabat, 2025)
This community service activity aims to introduce information technology to students in grades 1 to 3 at SD Madison School Mobuya. Through an interactive workshop approach, students were introduced to information technology tools and basic computer components. A total of 28 students participated in this activity, starting with a pretest to assess their initial understanding of technology. The pretest results showed that 80% of students were not familiar with technological tools and 90% were not familiar with the parts of a computer. After participating in the educational sessions, the posttest results revealed that all students had gained a solid understanding of information technology tools and basic computer components. This activity proves that early introduction to information technology can improve students' understanding of technology and equip them with basic skills needed to face the challenges of the digital world. It is hoped that this activity can be replicated in other schools to broaden the positive impact on the development of technology literacy among students.